2011
DOI: 10.21082/ijas.v12n1.2011.p40-46
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutrition and Glycemic Index of Sweet Potatoes and Its Appropriate Processing to Hypoglycemic Foods

Abstract: <p>Indonesia placed the fourth biggest diabetics in the world after India, China, and the USA with prevalence amounting to 8.6% of the population. Diabetes is an abnormal carbohydrate metabolism. Therefore, nutrition plays a key role in the management of the disease. This study aimed to find hypoglycemic sweet potatoes and appropriate processing to create low glycemic foods. Eight Indonesian sweet potato varieties/clones were used in this experiment, i.e. Kidal, Sukuh, Sari, Ungu, Jago, BB00105.10, B0464… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
4
9
0
4
Order By: Relevance
“…The studies shown that, there was a positive correlation between consumption of foods with high glycemic index and increased risk of chronic disease such as diabetes [21]. The nutrition plays a key role in the management and treatment of diabetes mellitus, thus foods with a low glycemic index can be beneficial in reducing the incidences of chronic diseases by avoid uncontrolled postprandial glucose load [13]. WHO recommended that the GI of foods be used in conjunction with information about food composition to guide food choices and at least 55% of energy be derived from carbohydrate and should be rich in dietary fiber and low glycemic index ranking [23].…”
Section: The Role Of Nutrition and Management Of Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies shown that, there was a positive correlation between consumption of foods with high glycemic index and increased risk of chronic disease such as diabetes [21]. The nutrition plays a key role in the management and treatment of diabetes mellitus, thus foods with a low glycemic index can be beneficial in reducing the incidences of chronic diseases by avoid uncontrolled postprandial glucose load [13]. WHO recommended that the GI of foods be used in conjunction with information about food composition to guide food choices and at least 55% of energy be derived from carbohydrate and should be rich in dietary fiber and low glycemic index ranking [23].…”
Section: The Role Of Nutrition and Management Of Diabetes Mellitusmentioning
confidence: 99%
“…It is also a good source of antioxidants, fiber, zinc, potassium, sodium, manganese, calcium, magnesium, iron, vitamin C and beta-carotene [12]. The hypoglycemic activity response of sweet potatoes is associated with their resistant starch and digestibility [13].…”
Section: Treads Of Root Crops Production Of Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation
“…Dilaporkan bahwa salah satu klon ubi jalar yang diolah dengan cara berbeda memiliki IG yang tidak sama. Ubi yang direbus memiliki nilai IG 62, digoreng nilai IG-nya menjadi 47 dan jika dipanggang nilai IG meningkat menjadi 80 8 .…”
Section: $%675$and7 6ul :Lgrzdwl +Hwl +Hudzdwl (Pd 6 0xo\dql )Dkpdunclassified
“…Tabel 3 menunjukkan kecenderungan peningkatan karbohidrat dan amilosa produk bihun, serta penurunan kadar protein. Data ini memperkuat hasil penelitian sejenis pada pada beras pratanak maupun pada olahan ubi jalar 6,8 . Perlakuan HMT, seperti perlakuan autoclavingcooling pada penelitian ini dapat mengubah sifat fungsional produk 9,15,16 .…”
Section: Komposisi Kimia Dan Sifat Fungsional Bihununclassified